Patent vitellointestinal duct with prolapsed (intussusceptions) of proximal and distal ileal loop: A case report - Dinesh D. Mundada; Satish P. Kapadnis (Elsevier, 2015)
A wide variety of anomalies may occur as a result of the vitellointestinal duct (VID) failing to obliterate completely. VID is well known because of its various complication and presentation most commonly due to Meckel's diverticulum. Small bowel prolapsed through patent VID is one of the rare presentations that have been reported. We are reporting a case of patent VID through which proximal and distal ileal segment had been intussuscepted and prolapsed through umbilicus.